Unraveling relationship between the genetic polymorphism CYP2A13 and nicotine metabolism of male smokers in Medan, Indonesia - Noni Novisari Soeroso; Rozaimah Zain-Hamid; Syamsul Bihar; Chaliza Soliha; Fannie Rizki Ananda; Aida (Egyptian Journal of Medical Human Genetics)
Abstract Background Nicotine metabolism significantly influences the levels of harmful nicotine metabolites in smokers. CYP2A13, a key enzyme in nicotine and xenobiotic metabolism, is implicated in tobacco smoke-related lung cancer. Aim This study investigated the association between CYP2A13 genetic polymorphism and nicotine metabolism in male smokers in Medan, Indonesia. Materials and methods This cross-sectional study included 66 male smokers (aged 20–65 years) who met pre-defined inclusion and exclusion criteria. Nicotine metabolite levels were quantified in urine samples using high-performance liquid chromatography (HPLC). CYP2A13 polymorphism was determined using polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) analysis of venous blood samples. Logistic regression analysis (Epi Info-7) assessed the association between CYP2A13 genotype and nicotine metabolism. Results No significant association (p > 0.05) was found between CYP2A13 genotype and nicotine metabolism. The CC genotype was most prevalent. The majority of participants exhibited rapid nicotine metabolism. Conclusion Further research with larger sample sizes and diverse populations is needed to elucidate the relationship between CYP2A13 genetic polymorphism and nicotine metabolism.